2018
DOI: 10.1073/pnas.1804060115
|View full text |Cite
|
Sign up to set email alerts
|

Distribution shapes govern the discovery of predictive models for gene regulation

Abstract: SignificanceSystems biology seeks to combine experiments with computation to predict biological behaviors. However, despite tremendous data and knowledge, biological models make less-accurate predictions compared with other fields. By analyzing single-cell, single-molecule measurements of mRNA during yeast stress response, we explore why and how the shapes of experimental distributions control prediction accuracy. We show how asymmetric data distributions with long tails cause standard modeling approaches to y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
184
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(190 citation statements)
references
References 40 publications
6
184
0
Order By: Relevance
“…In this article, we adopted a Markov chain Monte Carlo algorithm with Metropolis-Hastings sampling (i.e., MCMC-MH) to compute the posterior distributions of the model parameters [15,45]. However, there is room to further improve the speed of Bayesian inference.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we adopted a Markov chain Monte Carlo algorithm with Metropolis-Hastings sampling (i.e., MCMC-MH) to compute the posterior distributions of the model parameters [15,45]. However, there is room to further improve the speed of Bayesian inference.…”
Section: Discussionmentioning
confidence: 99%
“…For example, application of noisy dynamical systems theory has shed light on cell-state transitions (Mojtahedi et al, 2016;Jin et al, 2018;Lin et al, 2018). Stochastic simulations of gene network dynamics have been used to develop and/or benchmark tools for network reconstruction (Schaffter et al, 2011;Dibaeinia and Sinha, 2019;Bonnaffoux et al, 2019) Stochastic model-aided analysis of single-cell measurements has been demonstrated to yield insights on gene regulatory mechanisms (Munsky et al, 2018). However, few existing analysis methods utilize discretemolecule, stochastic models, which fully account for intrinsic gene expression noise and its impact on cell-state, to aid in the interpretation of noisy distributions recovered from single cell RNA sequencing data.…”
Section: Introductionmentioning
confidence: 99%
“…Studies at single-cell resolution are crucial to this, enabling the full distribution of expression levels to be obtained over a population of cells. Such data not only provides qualitative insight into the variability between cells, but can also enable the inference of the underlying dynamical processes ( Munsky et al, 2018 ), through the combination of biological insight and quantitative models. This is the approach we take here to investigate the sources of noise that lead to heterogeneity of nifHDK gene expression at the transcriptional level.…”
Section: Introductionmentioning
confidence: 99%